Pengenalan Teknologi Pertanian Artifical Lighting Berbasis IoT Pada Civitas Akademik SMK Yasti Cisaat Sukabumi - Mas Aly Afandi; Anggun Fitrian Isnawati; Reni Dyah Wahyuningrum; Ezi Rohmat; Abi Hakim Amanullah; Andri Juli Setiawan; Indrarini Dyah Irawati; Sugondo Hadiyoso; Dadan Nur Ramadan; Yudha Purwanto; Fairuz Azmi; Arfianto Fahmi (Madani : Indonesian Journal of Civil Society, 2023)
Technological developments in the Internet of Things (IoT) are growing rapidly, especially in agriculture. The lack of understanding of the development of IoT is the basis for the service team to conduct training for students and teachers. The service is carried out by the socialization method to students regarding IoT for agriculture. In practice, community service utilizes hydroponics that has been built in the SMK Yasti Cisaat Sukabumi area. After evaluating the implementation of community service, it can be seen that students have succeeded in understanding IoT based on artificial lighting and successfully implementing IoT tools in the school's hydroponic home. At the end of the activity, feedback is given as an effort to evaluate this community service activity. There are 5 statements in the questionnaire with an average result of 94.8%. These results show that the community service partners are very satisfied with the IoT training and hydroponic implementation.